Transcriptomic-based Characterization of Streptomyces-Yeast Interactions - Kauro, Aleksi (My University, 2025)
The global rise in antimicrobial resistance is a critical public health threat, causing millions of deaths worldwide. This urgent crisis necessitates the discovery of novel antibiotics. Streptomyces species are well known for their ability to produce a diverse range of bioactive secondary metabolites and have long been a focal point of natural product research aimed at antibiotic discovery. In this study, the activation of silent biosynthetic gene clusters (BGCs) in Streptomyces peucetius ATCC 27952 was investigated through co-cultivation with inactive Saccharomyces cerevisiae cells to stimulate secondary metabolite production. Additionally, the genome of S. peucetius ATCC 27952 was analysed for its BGC content. This approach led to the identification of four transcriptionally active and potentially novel BGCs (regions 5, 10, 16, and 21), each exhibiting distinct activation patterns in response to the presence of yeast cells. Notably, the early activation of certain BGCs suggested that microbial interactions, even in the absence of live cells, can trigger secondary metabolism. Future research should focus on identifying the metabolic products of these activated BGCs using multi-omics approaches and functionally characterize both the BGCs and their products. Additionally, machine learning tools represent a promising avenue for BGC identification and could be integrated into future workflows. These further investigations would not only deepen our understanding of secondary metabolite biosynthesis but would also contribute to the discovery of novel antibiotics.
Keywords: Streptomyces, transcriptomics, secondary metabolism, biosynthetic gene cluster, natural products, genome mining